PENGARUH PERSEPSI NILAI, CITRA MEREK DAN PERSEPSI HARGA TERHADAP MINAT BERKUNJUNG (Studi kasus pada Jawa Timur Park 3 Kota Wisata Batu) - Virza Aliffudy; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis research was conducted with the aim of analyzing the influence of Perception of Value, Brand Image and Price Perception on Interest in Visiting East Java Park 3, the sample of this study was 86 visitors who were made as respondents. Based on the results of hypothesis testing, the simultaneous perception of value, brand image and price perception has an influence on interest in visiting East Java Park 3. Perceived value, brand image and price perception partially has an influence on interest in visiting East Java Park 3.Keyword: Perception of Value, Brand Image and Price Perception, Visiting Interest.